Energy return on investment for alternative jet fuels. (1st March 2015) - Trivedi, Parthsarathi; Olcay, Hakan; Staples, Mark D.; Withers, Mitch R.; Malina, Robert; Barrett, Steven R.H.
Highlights: Definition and comparison of three variants of the energy return on investment (EROI) metric. Application of EROI to conventional and alternative jet fuel production pathways. The relative ranking of results for alternative and conventional jet fuel pathways is dependent on the definition of EROI. Total energy input requirements are the lowest for conventional jet fuel. Abstract: We quantify energy return on energy investment (EROI) as one metric for the sustainability of alternative jet fuel production. Lifecycle energy requirements are calculated and subsequently used for calculating three EROI variants. EROI1 is defined as the ratio of energy in fuel output to lifecycle (direct and indirect) fossil fuel energy inputs, excluding the energy content of fossil feedstock that ends up in the produced fuel. EROI2 is defined as the ratio of energy in fuel output to total fossil fuel energy inputs, including the energy content of fossil feedstock that ends up in the produced fuel. EROI3 is defined as the ratio of energy in fuel output to lifecycle (direct and indirect) fossil and non-fossil energy inputs, excluding the energy content of fossil and non-fossil feedstock that ends up in the produced fuel. We also define an approximation for EROI1 using lifecycle CO2 emissions. This approach agrees to within 20% of the actual EROI1 and can be used as an alternative when necessary. The feedstock-to-fuel pathways considered include conventional jet fuel from crude oil; Fischer–Tropsch jet (FT-J) fuel from natural gas (NG), coal and/or switchgrass; hydroprocessed esters and fatty acids jet (HEFA-J) fuel from soybean, palm, rapeseed and jatropha; and advanced fermentation jet (AF-J) fuel from sugarcane, corn grain and switchgrass. We find that EROI1 for jet fuel from conventional crude oil ranges between 4.9 and 14.0. Among the alternative fuel pathways considered, FT-J fuel from switchgrass has the highest baseline EROI1 of 9.8, followed by AF-J fuel from sugarcane at 6.7. HEFA-J fuel from oily feedstocks has an EROI1 between 1.6 (rapeseed) and 2.9 (palm). EROI2 differs from EROI1 only in the case of fossil-based jet fuels. Conventional jet from crude oil has a baseline EROI2 of 0.9, and FT-J fuel from NG and coal have values of 0.6 and 0.5, respectively. EROI3 values are on average 36% less than EROI1 for HEFA-J pathways. EROI3 for the AF-J and FT-J fuels considered is 50% less than EROI1 on average. All alternative fuels considered have a lower baseline EROI3 than conventional jet fuel.